Domestic and international tourists preference in a homestay programmes : a case study of Dorani Homestay, Selangor - Nur Ili Izyani binti Muhamad (Kulliyyah Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
At present, the Dorani Homestay programme becomes one of the recognized tourism programme in the tourism industry. However, several of the homestay programme in Dorani Homestay needs an improvement to meet the preference level of the domestic and international tourists. This research aims to create the tourism programme offered by Dorani Homestay suit the domestic and international tourists.The objectives of the study are to review the program provided by the Dorani Homestay to the domestic and international visitors, to investigate of domestic and international tourist preference in the homestay programme and to suggest the improvement of the homestay programme based on domestic and international tourist preference. The method of data collection was divided into two (2) parts, which are primary and secondary data. These both data collections are used in this research. Primary data will be collected during site visits, through site survey and observation. For secondary data, it will be gathered through literature reviews for qualitative information. Specific approaches and techniques for data collection applied in this study are literature reviews, site survey and observation as well questionnaires. The data analyzed through SPSS software for the frequency of the visitors' background, travel information and tourist preference level. Meanwhile, the Relative Important Index (RII) was gathered to calculate the preference level of the local and foreign tourist towards the homestay programme at Dorani Homestay.Through the result achieved, the majority of the domestic visitors preferred the environment, food, and beverage as well the activities offered at Dorani Homestay. In contrast, for the international tourists, their preference level is focused on the food and beverage, accommodation and services.It can be concluded that other attributes of the homestay programme which recorded as least preference level for both groups have to improve immediately by the Dorani Homestay host to fully meet the preference level of domestic and international guests currently and in future. Several recommendations proposed based on every single of findings in all parts of questions such as; approaches to overcome the hot weather and temperature of local climate, improve and propose varieties of traditional food and beverage as well an activity, improve the quality of accommodation and activity center, upgraded inadequate services, enhance the methods of promotion and advertisement also develop the accessibility aspects.